2016
DOI: 10.18632/oncotarget.12997
|View full text |Cite
|
Sign up to set email alerts
|

Defective ciliogenesis in thyroid hürthle cell tumors is associated with increased autophagy

Abstract: Primary cilia are found in the apical membrane of thyrocytes, where they may play a role in the maintenance of follicular homeostasis. In this study, we examined the distribution of primary cilia in the human thyroid cancer to address the involvement of abnormal ciliogenesis in different thyroid cancers. We examined 92 human thyroid tissues, including nodular hyperplasia, Hashimoto's thyroiditis, follicular tumor, Hürthle cell tumor, and papillary carcinoma to observe the distribution of primary cilia. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…For example, tubulin glycylation was previously shown to control PC length in vitro . In addition, it has been reported that PC length can be altered in some human tumor tissues . Future studies will reveal whether PTM patterns in PC could serve as a biomarker and how altered length could modulate the function of PC during tumorigenesis.…”
Section: General Considerations and Remarksmentioning
confidence: 95%
“…For example, tubulin glycylation was previously shown to control PC length in vitro . In addition, it has been reported that PC length can be altered in some human tumor tissues . Future studies will reveal whether PTM patterns in PC could serve as a biomarker and how altered length could modulate the function of PC during tumorigenesis.…”
Section: General Considerations and Remarksmentioning
confidence: 95%
“…In thyroid epithelial cells, primary cilia protrude from the apical surface into the follicular luminal space, which contains colloid; the primary cilia sense the environment of the follicular lumen and contribute to follicular function, including production of hormone . Whereas the distribution and length of cilia facing the follicular lumen are uniform across variable‐sized follicles in the normal thyroid gland, most HCs found in benign and malignant thyroid diseases are devoid of primary cilia . Intracytoplasmic lumen (ICL) is defined as cytoplasmic vacuoles with or without magenta material inside in Diff–Quik stained or vacuoles with or without greenish material inside Papanicolaou stained smears .…”
Section: Discussionmentioning
confidence: 99%
“…34 Whereas the distribution and length of cilia facing the follicular lumen are uniform across variable-sized follicles in the normal thyroid gland, most HCs found in benign and malignant thyroid diseases are devoid of primary cilia. 35 Intracytoplasmic lumen (ICL) is defined as cytoplasmic vacuoles with or without magenta material inside in Diff-Quik stained or vacuoles with or without greenish material inside Papanicolaou stained smears. 36 The cytoplasmic vacuoles demonstrate positive immunoreactions for thyroglobulin in both aspirate smears and tissue sections.…”
Section: Assessment Of Frequency Of Cases With Hcs and Intracytoplasmmentioning
confidence: 99%
“…Interestingly, although PTCs have long cilia, Hürthle cells found either in benign nodules or in malignant thyroid diseases were devoid of primary cilia (Lee et al 2016). Loss of cilia seemed to be a characteristic feature of Hürthle cells and was associated with high levels of autophagosome biogenesis, and inhibition of autophagy restored ciliogenesis in the Hürthle cell lines (Lee et al 2016).…”
Section: Autophagy In Initiation and Development Of Thyroid Cancersmentioning
confidence: 99%